FFECT ON META-ANALYSES OF DRUG TRIALS: DISTINCT COMPANY META-ANALYSIS - R.RAJESHKANNAN; MITHILESH K.SINGH (International Journal of Pharma and Bio Sciences, 2016)
To deal with quality, influence of the product of the same medicine of different companies in India we are going to provide all the details needs by the users. Like the quality of each medicine of different companies year wise based on the user review and influence on patient. Firstly, this report introduces the report of the medicine which is used in day to day life and we do not have any idea of the quality of that company. Secondly, it will show in different periods and their characteristics in different perspective, aiming to explore and analyse the findings and examines the impacts of the quality of the medicine based on the customer’s feedbacks and reviews. We will take the quality report from the different sources and will analyse it based on that reports and will provide the best report based on all these information. To work on this report, we are using the business analytical tool for better user experience that will a provide different angle of the information like in pie chart, dash chart, graphical view and year report. Medical performance management (MPM) is a key business initiative that enables companies to align strategic and operational objectives with business activities in order to fully manage the quality of medicine through better informed decision making and action. Effective medical performance requires an organization to model and monitor not only its tactics, but also its strategies and the assumption on which these strategies are built. Here the question is not that the customer are choosing right product or bad product, the question is, because of every bad choice and bad product patient are getting more problem or getting more time to recover from their issue or some time they are effected in a bad way and losing their life so this is not a one way, this is two way effect on the patient. Finally, we have come to concluding that the quality and influence of medicine not only based on the name of the medicine but also on the company which is making this medicine.